Cancer predisposition syndromes: lessons for truly precision medicine - Glaire, M; Brown, M; Church, D; Tomlinson, I (John Wiley & Sons Ltd, 2016)
Cancer predisposition syndromes are typically uncommon, monogenic, high-penetrance disorders. Despite their rarity, they have proven to be highly clinically relevant in directing cancer prevention strategies. As such, they share notable similarities with an expanding class of low-frequency somatic mutations that are associated with a striking prognostic or predictive effect in the tumours in which they occur. In this review, we highlight these commonalities, with particular reference to mutations in the proofreading domain of replicative DNA polymerases. These molecular phenotypes may occur as either germline or somatic events, and in the latter case have been shown to confer a favourable prognosis and potential increased benefit from immune checkpoint inhibition. We note that incorporation of these variants into clinical management algorithms will help refine patient management, and that this will be further improved by the inclusion of other germline variants, such as those that determine the likelihood of benefit or toxicity from anti-neoplastic therapy. Finally, we propose that such integrated patient and tumour profiling will be essential if we are to deliver truly precision medicine for cancer patients, but in a similar way to rare germline mutations, we must ensure that we identify and utilise rare somatic mutations with strong predictive and prognostic effects.